Influence of Subwavelength Grating Asymmetry on Long-Wavelength Infrared Transmittance Filters - Michael Barrow; Marty Scherr; Jamie Phillips (IEEE Photonics Journal, 2018)
Subwavelength dielectric gratings provide a means of narrowband spectral filtering by coupling to quasi-guided leaky modes, providing a high reflectivity background and narrowband transmittance via Fano resonance behavior. Geometrically asymmetric two-step gratings enable normal incidence filtering by accessing symmetry-protected leaky modes. The impact of asymmetry on leaky mode coupling and optical filter response are studied via simulation and described by the Fano resonance theory. The influence of asymmetry introduced by grating step height and angular cone of incidence are verified experimentally in silicon/air gratings in the long-wavelength infrared (8–14 μm).